Offshore photovoltaic cable material composition as well as preparation method and application thereof

By designing the multi-dimensional crosslinking network structure of cable materials, the existing photovoltaic cable materials have been solved, and the materials have excellent heat resistance, moisture and heat resistance, salt spray corrosion resistance and flame retardancy are achieved, meeting the high standards requirements of offshore photovoltaics.

CN119798819APending Publication Date: 2025-04-11JIANGSU DASHENG POLYMER
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411981215.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing photovoltaic cable materials are difficult to meet the requirements of harsh conditions such as high salt, high humidity, high temperature and sun exposure in marine environments, resulting in insufficient corrosion resistance and heat resistance.

Method used

By designing and combining the components of cable materials, a stable multi-dimensional crosslinking network structure is formed, including polyethylene, butadiene-based polymers, thermoplastic elastomers, alkenyl cyclophosphazene compounds and alkenyl oligosilsesquioxanes, etc., to improve the mechanical properties, heat resistance, moisture and heat resistance of the material.

Benefits of technology

It has achieved excellent heat resistance, humidity and heat resistance, salt spray corrosion resistance and flame retardant cable materials in offshore photovoltaic applications, meeting the long-term safe and stable operation needs under harsh conditions at sea.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221599450000031
    Figure BDA0005221599450000031
  • Figure BDA0005221599450000061
    Figure BDA0005221599450000061
  • Figure BDA0005221599450000091
    Figure BDA0005221599450000091
Patent Text Reader

Abstract

The invention provides an offshore photovoltaic cable material composition as well as a preparation method and application thereof, and the cable material composition is prepared from the following raw materials in parts by mass: 60 to 85 parts of polyethylene, 1 to 20 parts of butadiene-based polymer, 5 to 25 parts of thermoplastic elastomer, 1 to 12 parts of compatilizer and 8 to 55 parts of alkenyl cyclophosphazene-containing compound, the flame retardant is prepared from the following components in parts by weight: 1-10 parts of vinyl oligomeric silsesquioxane, 2-10 parts of alkenyl oligomeric silsesquioxane, 0.1-5 parts of a crosslinking agent, 0.1-5 parts of an assistant crosslinking agent and 30-90 parts of a flame retardant. Through design and mutual compounding of the components, a specific multi-dimensional cross-linked network structure is formed in the cable material, so that the cable material composition has excellent mechanical properties, heat resistance, humidity and heat resistance, salt spray corrosion resistance and flame retardance, and can meet the high-standard requirements of offshore photovoltaic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of cable materials, and in particular relates to a cable material composition for offshore photovoltaics, a preparation method and an application thereof. Background Art

[0002] As the global demand for renewable energy continues to grow, offshore photovoltaics, as an emerging clean energy technology, has gradually attracted widespread attention. By building solar photovoltaic power generation systems in offshore and tidal flats and other marine environments, offshore photovoltaics can effectively utilize vast marine resources, improve photovoltaic power generation efficiency, reduce the occupation of land resources, and reduce the impact on the environment. Cables are energy transmission components in photovoltaic power generation systems and play a key role in offshore photovoltaic power generation. The research on cable materials is of great significance to the stable operation of photovoltaic power generation systems and the rapid development of green energy.

[0003] CN107141650A discloses an anti-aging photovoltaic cable material, comprising the following components: 18-33 parts of polyvinyl chloride, 10-30 parts of chlorinated butadiene rubber, 1-7 parts of a cross-linking agent, 2-8 parts of modified pyrophyllite, 27-41 parts of a flame retardant, 3-9 parts of an anti-aging agent, 5-9 parts of a maleic anhydride grafted compatibilizer, 2-6 parts of a Ca / Zn composite stabilizer, 1-4 parts of magnesium stearate, and 0.1-0.2 parts of trioctyl phosphite. The anti-aging photovoltaic cable has excellent performance in anti-aging, high temperature resistance and flame retardancy.

[0004] CN103881166A discloses a low-smoke halogen-free flame retardant material for photovoltaic cables, comprising the following components in mass percentage: 30-35% rubber, 6-10% polyolefin resin, 6-10% filler oil, 48-56% halogen-free flame retardant, 0.5-3% hydrophobic modifier, 0.1-1% antioxidant, 0.1-1% lubricant, 0.5-2% carbon black, and 0.1-0.5% other additives; wherein the rubber is a mixture of one or more of polybutadiene rubber, silicone rubber, and ethylene-propylene rubber; and the polyolefin resin is a mixture of one or more of polyethylene resin, polypropylene resin, and ethylene-vinyl acetate copolymer. The low-smoke halogen-free flame retardant material has good insulation, good water resistance, acid and alkali corrosion resistance, and high and low temperature resistance.

[0005] CN117777586A discloses a sheath material for offshore photovoltaic cables, comprising the following raw material components: 5-15 parts of maleic anhydride grafted EPDM rubber, 10-20 parts of ethylene-vinyl acetate copolymer, 13-22 parts of ethylene-octene copolymer, 0.5-1.5 parts of multifunctional crosslinking agent, 45-65 parts of flame retardant, 5-10 parts of synergistic flame retardant, 0.5-2 parts of antioxidant, 1-3 parts of lubricant, 1-2 parts of silane coupling agent, 0.5-1.2 parts of mildewproof agent, and 0.8-1.5 parts of graphene. The sheath material is obtained by crosslinking through electron accelerator irradiation, and has good performance in salt spray resistance, mildew resistance, flame retardancy, heat resistance, aging resistance, etc.

[0006] Offshore photovoltaic cables need to be able to withstand harsh conditions such as high salt, high humidity, high temperature and exposure in the marine environment, which requires the cable materials to have excellent corrosion resistance and heat resistance. However, the current photovoltaic cable materials cannot adapt well to the harsh marine environment and are difficult to meet the high standards of offshore photovoltaics. In order to solve these problems, the industry has tried to use corrosion-resistant materials, surface coating protection, and additional protective measures, but these methods are difficult to implement and costly. In addition, they will age and crack in harsh environments for a long time, and cannot fundamentally solve the corrosion and heat resistance problems of photovoltaic cables.

[0007] Therefore, developing a cable material with excellent heat resistance, moisture and heat resistance, and corrosion resistance to meet the application requirements of offshore photovoltaics is an urgent problem to be solved in this field. Summary of the invention

[0008] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a cable material composition for offshore photovoltaics, a preparation method and application thereof. Through the design and synergistic compounding of the components, a stable and reliable cross-linking system is formed in the material, so that the cable material composition has excellent heat resistance, moisture and heat resistance, salt spray corrosion resistance and flame retardancy. It is used in offshore photovoltaics and can fully meet the needs of long-term safe and stable operation under harsh conditions.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a cable material composition for offshore photovoltaics, wherein the raw materials for preparing the cable material composition include the following components in parts by mass:

[0011]

[0012] In the preparation raw materials of the present invention, the polyethylene, butadiene-based polymer and thermoplastic elastomer jointly construct a polymer matrix component. The introduction of a compatibilizer can improve the compatibility of each organic component, and compounded with a cross-linking agent and a co-cross-linking agent, a stable cross-linking structure can be formed through a cross-linking reaction of a free radical mechanism, thereby increasing the degree of cross-linking and improving the mechanical properties, heat resistance, moisture and heat resistance and salt spray corrosion resistance of the cable material.

[0013] In the preparation raw materials of the present invention, the alkenyl cyclophosphazene compound is a reactive nitrogen-phosphorus flame retardant, and the alkenyl oligomeric silsesquioxane contains alkenyl and Si-O-Si skeleton structures. On the one hand, the three components of the nitrogen-phosphorus flame-retardant alkenyl cyclophosphazene compound, the silicon flame-retardant alkenyl oligomeric silsesquioxane, and the flame retardant are compounded to synergistically exert an excellent flame retardant effect; on the other hand, the alkenyl functional groups in the alkenyl cyclophosphazene compound and the alkenyl oligomeric silsesquioxane react with an organic system (including polyethylene, butadiene-based polymers, thermoplastic elastomers, crosslinking agents, auxiliary crosslinking agents, etc.), and the cyclophosphazene structure and the Si-O-Si skeleton are embedded in the crosslinking network in the form of covalent bonds, so that the cable material has an intrinsic flame retardant effect, and at the same time, a multidimensional crosslinking system containing carbon-carbon bonds, nitrogen-phosphorus rings and Si-O-Si structures is constructed, which not only improves the mechanical properties and heat resistance of the cable material, but also can block the intrusion of water vapor, and significantly improves the moisture heat resistance and salt spray corrosion resistance of the cable material.

[0014] Therefore, the present invention, through the design and mutual compounding of each component, synergistically forms a specific multi-dimensional cross-linked network structure, so that the cable material composition has excellent mechanical properties, heat resistance, moisture and heat resistance, salt spray corrosion resistance and flame retardancy, can be used for offshore photovoltaics, and fully meet the needs of long-term safe and stable operation under harsh conditions at sea.

[0015] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0016] In the preparation raw materials of the present invention, the mass parts of the polyethylene are 60-85 parts, for example, it can be 62 parts, 65 parts, 68 parts, 70 parts, 72 parts, 75 parts, 78 parts, 80 parts, 82 parts or 84 parts, as well as specific point values ​​between the above point values. Due to limited space and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0017] The mass fraction of the butadiene-based polymer is 1-20 parts, for example, it can be 2 parts, 5 parts, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 15 parts, 16 parts or 18 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0018] The mass proportion of the thermoplastic elastomer is 5-25 parts, for example, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 15 parts, 16 parts, 18 parts, 20 parts, 22 parts or 24 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0019] The mass fraction of the compatibilizer is 1-12 parts, for example, it can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0020] The mass parts of the alkenyl cyclophosphazene-containing compound are 8-55 parts, for example, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, 45 parts, 48 ​​parts, 50 parts, 52 parts or 55 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0021] The mass fraction of the alkenyl oligomeric silsesquioxane is 2-10 parts, for example, it can be 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0022] The mass fraction of the cross-linking agent is 0.1-5 parts, for example, it can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4 parts, 4.2 parts, 4.5 parts or 4.8 parts, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0023] The weight percentage of the auxiliary cross-linking agent is 0.1-5 parts, for example, it can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4 parts, 4.2 parts, 4.5 parts or 4.8 parts, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0024] The mass parts of the flame retardant are 30-90 parts, for example, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts or 85 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0025] Preferably, the alkenyl cyclophosphazene compound has a structure as shown in Formula I:

[0026]

[0027] In Formula I, R1, R2, R3, R4, R5, and R6 are each independently selected from any one of a phenyl group and a C2-C10 alkenyl-substituted phenyl group, and at least one (e.g., 2, 3, 4, 5, 6) of R1, R2, R3, R4, R5, and R6 is a C2-C10 alkenyl-substituted phenyl group.

[0028] In the present invention, the C2-C10 alkenyl group may be a straight chain or branched alkenyl group of C2, C3, C4, C5, C6, C7, C8, C9, or C10, containing at least one C=C, illustratively including but not limited to vinyl, propenyl, allyl, butenyl, pentenyl, hexenyl, heptenyl, octenyl, nonenyl, decenyl, butadienyl, pentadienyl, and the like.

[0029] Preferably, R1, R2, R3, R4, R5, and R6 are each independently selected from phenyl, Any one of, and at least one of R1, R2, R3, R4, R5 and R6 is -* indicates the attachment site of the group.

[0030] R is selected from any one of C2-C10 (e.g., C3, C4, C5, C6, C7, C8, C9, etc.) alkenyl groups, preferably vinyl, propenyl or allyl.

[0031] Among the R1, R2, R3, R4, R5 and R6 The number is 1-6, such as 1, 2, 3, 4, 5 or 6, preferably 2-6.

[0032] Preferably, the alkenyl oligomeric silsesquioxane has a polyhedral structure, and is preferably an alkenyl-containing cage-shaped oligomeric silsesquioxane.

[0033] Preferably, the alkenyl oligomeric silsesquioxane includes any one of octavinyl cage oligomeric silsesquioxane, octamethacrylate cage oligomeric silsesquioxane, octaacrylate cage oligomeric silsesquioxane, octaacryloxy cage oligomeric silsesquioxane, octamethacryloxy cage oligomeric silsesquioxane, and methacryloxypropyl cage polysilsesquioxane, or a combination of at least two thereof.

[0034] Preferably, the mass ratio of the alkenyl oligomeric silsesquioxane to the alkenyl cyclophosphazene-containing compound is 1:(3-8), for example, 1:3.2, 1:3.5, 1:4, 1:1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7 or 1:7.5, etc.

[0035] As a preferred technical solution of the present invention, the mass ratio of the alkenyl oligomeric silsesquioxane to the alkenyl cyclophosphazene compound is 1:(3-8), which together with the flame retardant forms a flame retardant system, so that the cable material composition achieves excellent flame retardant effect; at the same time, the alkenyl oligomeric silsesquioxane, the alkenyl cyclophosphazene compound and the components such as the co-crosslinking agent, the butadiene polymer, the thermoplastic elastomer and the polyethylene undergo free radical crosslinking reaction, forming a multidimensional crosslinking system containing carbon-carbon bonds, nitrogen-phosphorus rings and Si-O-Si structures in the cable material, so that the cable material composition has excellent mechanical properties, heat resistance, moisture resistance and salt spray corrosion resistance. If the mass ratio of the alkenyl oligomeric silsesquioxane to the alkenyl cyclophosphazene compound exceeds the preferred range of the present invention, it will not only affect the flame retardant properties, but also reduce the stability of the cable material under harsh conditions such as high temperature, moisture, and high salt.

[0036] Preferably, the polyethylene includes any one of linear low-density polyethylene (LLDPE), high-density polyethylene (HDPE), and metallocene polyethylene, or a combination of at least two thereof, and a combination of high-density polyethylene and metallocene polyethylene is further preferred.

[0037] As a preferred technical solution of the present invention, the polyethylene includes a combination of HDPE and metallocene polyethylene, HDPE has high hardness, and has excellent performance in tensile strength, toughness, creep and chemical stability, and metallocene polyethylene is a linear polyethylene prepared by catalysis using a metallocene (MAO) catalyst, which has a regular molecular chain structure, good processing performance, and high elongation at break. The combination of HDPE and metallocene polyethylene as a polyethylene matrix can improve the mechanical properties and processing properties of the cable material composition.

[0038] Preferably, the mass percentage of metallocene polyethylene in the polyethylene is 15-50%, for example, it can be 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45% or 48%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0039] Preferably, the melt index of the metallocene polyethylene at 190°C and 2.16kg is 0.02-10g / 10min, for example, it can be 0.1g / 10min, 0.3g / 10min, 0.5g / 10min, 0.8g / 10min, 1g / 10min, 1.5g / 10min, 2g / 10min, 2.5g / 10min, 3g / 10min, 3.5g / 10min, 4g / 10min, 4.5g / 10min, 5g / 10min, 6g / 10min, 7g / 10min, 8g / 10min or 9g / 10min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 0.05-6g / 10min is further preferred.

[0040] Preferably, the butadiene-based polymer includes any one of polybutadiene and butadiene-styrene copolymer, or a combination of at least two thereof.

[0041] Preferably, the number average molecular weight of the butadiene-based polymer is 1000-10000, for example, it may be 2000, 3000, 4000, 5000, 6000, 7000, 8000 or 9000, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0042] Preferably, the butadiene-based polymer comprises a structural unit represented by Formula II.

[0043]

[0044] Preferably, the molar percentage of the structural unit represented by formula II in the butadiene-based polymer is 20-90%, for example, it can be 25%, 30%, 35%, 40%, 45%, 50%, 52%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 88%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 40-90% is further preferred.

[0045] In the present invention, the butadiene-based polymer contains a 1,2-vinyl structure shown in formula II, and the side chain vinyl has a high reactivity, and can undergo a free radical crosslinking reaction with a crosslinking aid, a thermoplastic elastomer, polyethylene, an alkenyl cyclophosphazene compound, an alkenyl oligomeric silsesquioxane and other components in the presence of a crosslinking agent, so as to form a specific multidimensional crosslinked network structure in the cable material, so that the cable material composition has excellent mechanical properties, heat resistance, moisture and heat resistance, and salt spray corrosion resistance. If the 1,2-vinyl structural unit shown in formula II is not contained or its content is too low, the crosslinking density of the cable material will be reduced, resulting in a decrease in the heat resistance, moisture and heat resistance, and salt spray corrosion resistance of the cable material.

[0046] Preferably, the mass ratio of the butadiene-based polymer to the thermoplastic elastomer is (0.5-2):1, for example, it can be 0.6:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1 or 1.9:1, etc.

[0047] In the present invention, the thermoplastic elastomer has excellent toughness, viscoelasticity and processing properties, and the butadiene-based polymer contains side chain alkenyl groups, which can provide abundant chemical crosslinking sites, and help improve the heat resistance, moisture and heat resistance and corrosion resistance of cable materials. As a preferred technical solution of the present invention, by controlling the mass ratio of butadiene-based polymer to thermoplastic elastomer to be (0.5-2): 1, the cable material composition achieves an excellent balance effect between processing properties, mechanical properties, heat resistance, salt spray corrosion resistance and moisture and heat resistance. If the mass ratio of the two exceeds the aforementioned range, it will affect the balance of various properties of the cable material, butadiene-based polymers too much will affect the elongation at break and processing properties of the material, and thermoplastic elastomers too much will reduce the heat resistance, moisture and heat resistance and corrosion resistance of the material.

[0048] Preferably, the thermoplastic elastomer includes POE elastomer and / or TPE elastomer, and POE elastomer is further preferred.

[0049] Preferably, the melt index of the thermoplastic elastomer at 190°C and 2.16kg is 1-20g / 10min, for example, it can be 2g / 10min, 3g / 10min, 4g / 10min, 5g / 10min, 6g / 10min, 7g / 10min, 8g / 10min, 9g / 10min, 10g / 10min, 12g / 10min, 14g / 10min, 15g / 10min, 16g / 10min or 18g / 10min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 1.2-8g / 10min is further preferred.

[0050] Preferably, the compatibilizer includes any one of maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, maleic anhydride grafted ethylene propylene diene monomer rubber, and maleic anhydride grafted ethylene-vinyl acetate copolymer, or a combination of at least two thereof.

[0051] Preferably, the cross-linking agent comprises an organic peroxide, and further preferably any one or a combination of at least two of isopropylbenzene hydroperoxide, di-tert-butyl peroxide, diisopropylbenzene hydroperoxide, dibenzoyl peroxide, cyclohexanone peroxide, tert-butyl perbenzoate, tert-butyl peracetate, tert-amyl peroxy (2-ethylhexyl) carbonate, di (4-methylbenzoyl) peroxide, 2,5-dimethyl-2,5-di-tert-butyl peroxide ethane, and tert-butyl peroxy-3,5,5-trimethylhexanoate.

[0052] Preferably, the auxiliary cross-linking agent is a compound containing at least 2 (≥2, such as 2, 3, 4, 5, 6, 8, etc.) unsaturated groups (such as alkenyl groups).

[0053] Preferably, the auxiliary crosslinking agent includes any one of triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, tri(1,2-propylene glycol) diacrylate, tri(2-hydroxyethyl) isocyanurate triacrylate, propoxylated trimethylolpropane triacrylate, or a combination of at least two thereof.

[0054] Preferably, the flame retardant includes any one of antimony trioxide, aluminum hydroxide, and magnesium hydroxide, or a combination of at least two of them.

[0055] Preferably, the preparation raw materials further include any one or a combination of at least two of a stabilizer, a lubricant, a silane coupling agent, a mildew preventer, an ultraviolet absorber, and an antioxidant.

[0056] Preferably, the preparation raw materials also include 0.1-5 parts of stabilizer by mass, and the mass parts of the stabilizer can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0057] Preferably, the stabilizer includes any one of calcium stearate, zinc stearate, magnesium stearate, and pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) or a combination of at least two thereof.

[0058] Preferably, the preparation raw material also includes 0.1-5 parts of lubricant by mass; the mass portion of the lubricant can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0059] Preferably, the lubricant includes any one of silicone masterbatch, silicone phenol, polyethylene wax, or a combination of at least two thereof.

[0060] Preferably, the preparation raw materials further include 0.1-3 parts of silane coupling agent by mass, and the mass parts of the silane coupling agent can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts or 2.8 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0061] Preferably, the silane coupling agent includes any one of a vinyl silane coupling agent, an epoxy silane coupling agent, an amino silane coupling agent, and a mercapto silane coupling agent, or a combination of at least two thereof.

[0062] Preferably, the silane coupling agent includes any one of methacryloxypropyltrimethoxysilane, acryloxypropyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloxy)propyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, and γ-aminoethylaminopropyltrimethoxysilane, or a combination of at least two thereof.

[0063] Preferably, the raw materials for preparation further include 0.1-5 parts of mildew preventer in parts by mass, and the parts by mass of the mildew preventer can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0064] Preferably, the mildew preventer includes any one of an organic mildew preventer, an inorganic mildew preventer, and a natural extract mildew preventer, or a combination of at least two of them.

[0065] Preferably, the preparation raw materials further include 0.1-3 parts of ultraviolet absorbers by mass, and the mass parts of the ultraviolet absorbers can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts or 2.8 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0066] Preferably, the ultraviolet absorber includes any one of a benzotriazole ultraviolet absorber, a salicylate ultraviolet absorber, a benzophenone ultraviolet absorber, a substituted acrylonitrile ultraviolet absorber, a triazine ultraviolet absorber, and a hindered amine ultraviolet absorber, or a combination of at least two thereof.

[0067] Preferably, the preparation raw materials further include 0.1-3 parts of antioxidants by mass, and the mass parts of the antioxidants can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts or 2.8 parts, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0068] Preferably, the antioxidant includes any one of a hindered phenol antioxidant, a hindered amine antioxidant, and a phosphite antioxidant, or a combination of at least two thereof.

[0069] In a second aspect, the present invention provides a method for preparing the cable material composition according to the first aspect, the preparation method comprising:

[0070] The prepared raw materials are mixed and extruded to obtain pellets;

[0071] The pellets are made into wires through a wire extruder, and the wires are irradiated and cross-linked through an electron accelerator to obtain the cable material composition.

[0072] The preparation method of the cable material composition provided by the present invention includes two cross-linking processes, wherein the first cross-linking is heat-induced cross-linking, which mainly occurs during the mixing process, so that a primary network structure with preliminary cross-linking is formed in the obtained granules; further, after the granules are processed into granules, they are irradiated and cross-linked by an electron accelerator, so that secondary cross-linking occurs in the material, and a specific multi-dimensional cross-linked network structure is obtained, so that the cable material composition has excellent mechanical properties, heat resistance, moisture and heat resistance, and salt spray corrosion resistance.

[0073] Preferably, the mixing is carried out in an internal mixer.

[0074] Preferably, the mixing temperature is 150-180°C, for example, it can be 155°C, 160°C, 162°C, 165°C, 168°C, 170°C, 172°C, 175°C or 178°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0075] Preferably, the mixing time is 5-30 min, for example, it can be 6 min, 8 min, 10 min, 12 min, 15 min, 18 min, 20 min, 22 min, 25 min or 28 min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0076] Preferably, the extrusion granulation is carried out in a screw extruder, such as a single-screw extruder or a twin-screw extruder.

[0077] Preferably, the operating temperature of the screw extruder is 100-150°C, for example, it can be 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C or 145°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 105-135°C is further preferred.

[0078] Preferably, the screw extruder comprises a first zone, a second zone, a third zone, a fourth zone, a fifth zone, a sixth zone and a seventh zone connected in sequence, and the temperature of each zone is independently 105-135°C, for example, it can be 108°C, 110°C, 112°C, 115°C, 118°C, 120°C, 122°C, 125°C, 128°C, 130°C, 132°C or 134°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0079] Preferably, the temperature of the first zone in the screw extruder is 105-115°C (e.g., 106°C, 108°C, 110°C, 111°C, 112°C, 113°C, 114°C or 115°C, etc.), the temperature of the second zone is 115-120°C (e.g., 115°C, 116°C, 117°C, 118°C, 119°C or 120°C, etc.), the temperature of the third zone is 115-120°C (e.g., 115°C, 116°C, 117°C, 118°C, 119°C or 120°C, etc.), and the temperature of the fourth zone is 120-125 ℃ (for example, 120℃, 121℃, 122℃, 123℃, 124℃ or 125℃, etc.), the temperature of the fifth zone is 120-125℃ (for example, 120℃, 121℃, 122℃, 123℃, 124℃ or 125℃, etc.), the temperature of the sixth zone is 120-130℃ (for example, 120℃, 122℃, 124℃, 126℃, 128℃ or 130℃, etc.), and the temperature of the seventh zone is 125-130℃ (for example, 125℃, 126℃, 127℃, 128℃, 129℃ or 130℃, etc.).

[0080] Preferably, the operating temperature of the wire extruder is 100-190°C, for example, it can be 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0081] Preferably, the wire extruder comprises a zone A, a zone B, a zone C and a zone D connected in sequence, so that the pellets can pass through zones A, B, C and D in sequence, wherein the operating temperature of zone A is 150-160°C (e.g., 152°C, 154°C, 155°C, 158°C, 159°C, etc.), the operating temperature of zone B is 165-175°C (e.g., 166°C, 168°C, 170°C, 172°C, 174°C, etc.), the operating temperature of zone C is 165-175°C (e.g., 166°C, 168°C, 170°C, 172°C, 174°C, etc.), and the operating temperature of zone D is 170-180°C (e.g., 172°C, 174°C, 175°C, 176°C, 178°C, etc.).

[0082] Preferably, the dose of the radiation cross-linking is 2-10 Mrad, for example, it can be 2.5 Mrad, 3 Mrad, 3.5 Mrad, 4 Mrad, 4.5 Mrad, 5 Mrad, 5.5 Mrad, 6 Mrad, 6.5 Mrad, 7 Mrad, 7.5 Mrad, 8 Mrad, 8.5 Mrad, 9 Mrad or 9.5 Mrad, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0083] In a third aspect, the present invention provides a use of the cable material composition as described in the first aspect in an offshore photovoltaic module.

[0084] Compared with the prior art, the present invention has the following beneficial effects:

[0085] (1) In the cable material composition provided by the present invention, the components are designed and compounded to cooperate with each other to construct a covalent cross-linking system comprising components such as polyethylene, butadiene-based polymers, thermoplastic elastomers, alkenyl cyclophosphazene compounds, alkenyl oligomeric silsesquioxanes, cross-linking agents and co-cross-linking agents, so as to form a specific multi-dimensional cross-linked network structure in the cable material, so that the cable material composition has excellent mechanical properties, heat resistance, moisture and heat resistance, salt spray corrosion resistance and flame retardancy, and can meet the high standards of offshore photovoltaics.

[0086] (2) Through the design and optimization of components, the present invention makes the tensile strength of the cable material composition ≥16.5MPa, the elongation at break ≥340%, the change rate of elongation at break after aging at 185°C for 168h ≤6%, the change rate of elongation at break after double 85 test for 168h ≤8%, the change rate of tensile strength after 30 days of salt spray test ≤10%, and can pass single vertical burning and mildew resistance tests, and has excellent comprehensive performance in mechanical properties, heat resistance, moisture and heat resistance, salt spray corrosion resistance, flame retardancy, mildew resistance, etc., and can be used for offshore photovoltaics, fully meeting the needs of long-term safe and stable operation under harsh offshore conditions. DETAILED DESCRIPTION

[0087] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0088] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0089] "Optionally", "optionally" or "either" means that the subsequently described matter or event can or cannot occur, and that the description includes cases where the event occurs and cases where it does not.

[0090] In the following specific implementation of the present invention, the specific information of the materials used is as follows:

[0091]

[0092]

[0093] The cable material composition and the preparation method thereof of the present invention will be described in detail below by taking a number of embodiments as examples, but the cable material composition and the preparation method thereof of the present invention are not limited to these embodiments.

[0094] Examples 1-10, Comparative Examples 1-6

[0095] A cable material composition, the raw materials for its preparation are shown in Table 1 and Table 2, and the unit of dosage of each component is "part".

[0096] The preparation method of the cable material composition is as follows:

[0097] (1) adding each component into a mixer according to the formula amount, premixing for 5 minutes to obtain a mixture; adding the mixture into an internal mixer, mixing at 165° C. for 20 minutes, and extruding and granulating through a single screw extruder to obtain pellets; the operating temperatures of zones 1 to 7 in the single screw extruder are 110° C., 115° C., 115° C., 120° C., 120° C., 125° C., and 125° C., respectively.

[0098] (2) adding the pellets obtained in step (1) into a wire extruder and extruding to obtain wires, wherein the operating temperatures of the AD zone in the wire extruder are 155° C., 170° C., 170° C., and 175° C., respectively; irradiating the wires with an electron accelerator for cross-linking, and the irradiation dose is 4 Mrad to obtain the cable material composition.

[0099] The cable material composition was tested for the following properties:

[0100] (1) Tensile strength and elongation at break: tested according to the method in standard GB / T 2951.11-2008.

[0101] (2) Heat resistance: After the cable material to be tested is aged at 185°C for 168 h, its elongation at break is tested and compared with the elongation at break measured in (1) to obtain the change rate; the change rate = the difference in elongation at break before and after aging / the original test value; the smaller the change rate, the better the heat resistance.

[0102] (3) Moisture and heat resistance: The cable material to be tested is placed in a moisture and heat aging test chamber at 85°C and 85% humidity. After 168 hours, the elongation at break is tested and compared with the elongation at break measured in (1) to obtain the change rate; the change rate = the difference in elongation at break before and after moisture and heat aging / original test value.

[0103] (4) Salt spray corrosion resistance: A salt spray cyclic corrosion test was performed according to the method in standard IEC 60068-2-52. The tensile strength was tested after 30 days and compared with the data measured in (1) to obtain the change rate; the change rate = the difference in tensile strength before and after salt spray corrosion / the original test value; the smaller the change rate, the better the salt spray corrosion resistance.

[0104] (5) Single vertical burning: Tested according to the method in GB / T 18380-2008.

[0105] (6) Mildew resistance: tested according to the method in standard GB / T 2423.16-2008.

[0106] The test results are shown in Table 1 and Table 2.

[0107] Table 1

[0108]

[0109]

[0110] Table 2

[0111]

[0112]

[0113]

[0114] According to the performance test data in Table 1, the present invention, through the design and joint action of each component in the raw material, makes it undergo a cross-linking reaction, forms a specific multi-dimensional covalent cross-linked network structure in the cable material, and makes the cable material composition have excellent mechanical properties, heat resistance, moisture and heat resistance, salt spray corrosion resistance, flame retardancy and mildew resistance. As some preferred technical schemes of the present invention, the tensile strength of the cable material composition provided by Examples 1-5 is 16.5-16.9MPa, the elongation at break is 340-356%, the elongation at break after aging at 185°C for 168h is 4.8-5.8%, the elongation at break after double 85 test for 168h is 6.3-7.5%, the tensile strength change rate of 30 days of salt spray test is 8.7-10%, can pass single vertical burning, mildew resistance grade is 0, has excellent mechanical properties, flame retardancy and mildew resistance, and can maintain excellent stability and reliability in harsh environments such as high temperature, high humidity, and high salt corrosion, and can meet the high standard requirements of offshore photovoltaics.

[0115] Further, in combination with the component formula and effect data of Example 1 and Example 6-10, it can be seen that the present invention realizes the regulation of covalent cross-linked structure by designing the content of 1,2-vinyl structural units in butadiene-based polymers, the dosage ratio of butadiene-based polymers to thermoplastic elastomers, and the dosage design and further optimization of alkenyl oligomeric silsesquioxanes and alkenyl-containing cyclophosphazene compounds, thereby synergistically improving the flame retardancy, mechanical properties, heat resistance, moisture and heat resistance, and salt spray corrosion resistance of cable materials. The 1,2-vinyl structural unit content of the butadiene-based polymer in Example 6 is relatively low, resulting in a slight decrease in the cross-linking density, which has a certain effect on the mechanical properties, heat resistance, moisture and heat resistance, and salt spray resistance of the cable material. The mass ratio of butadiene-based polymer to thermoplastic elastomer in Examples 7-8 exceeds the preferred (0.5-2): 1 of the present invention, resulting in varying degrees of increase in the rate of change of tensile strength and elongation of the cable material under high temperature, high humidity, and salt spray corrosion conditions. The dosage ratio of alkenyl oligomeric silsesquioxane to alkenyl cyclophosphazene-containing compound in Examples 9-10 exceeds the preferred 1:(3-10) of the present invention. Although it can pass the single vertical combustion test, the mechanical properties, heat resistance, moisture and heat resistance and corrosion resistance of the cable material are reduced to varying degrees.

[0116] In the cable material composition provided by the present invention, by designing and compounding each component, the components are coordinated with each other to construct a covalent cross-linking system including polyethylene, butadiene-based polymer, thermoplastic elastomer, alkenyl cyclophosphazene compound, alkenyl oligomeric silsesquioxane, cross-linking agent and auxiliary cross-linking agent, etc., and the cable material has a specific multi-dimensional cross-linked network structure, so that it has excellent flame retardancy, mechanical properties, heat resistance, moisture and heat resistance and salt spray corrosion resistance. Comparison of Table 1 and Table 2 shows that Comparative Example 1 does not contain butadiene-based polymers, and Comparative Example 2 contains hydrogenated SEBS. Since the system does not contain reactive side chain vinyl, the cross-linking degree of the cable material is insufficient, resulting in a significant reduction in its tensile strength, elongation, heat resistance, moisture and heat aging resistance and corrosion resistance. Comparative Example 3 uses alkenyl-free hexaphenoxy cyclotriphosphazene, and Comparative Example 4 uses alkenyl-free oligomeric silsesquioxane, so it can only play a flame retardant role as an additive flame retardant, but cannot participate in the construction of a covalent cross-linked network, resulting in a decrease in the mechanical properties, heat resistance, moisture and heat resistance, and corrosion resistance of the cable material. Comparative Example 5 does not contain alkenyl oligomeric silsesquioxane, and Comparative Example 6 does not contain cyclophosphazene compounds. The cable material does not form a synergistic flame retardant system of nitrogen, phosphorus, and silicon, nor does it have a specific cross-linked network, resulting in a comprehensive deterioration in the flame retardancy, mechanical properties, heat resistance, moisture and heat resistance, and salt spray corrosion resistance of the material. Comparative Example 7 does not contain a cross-linking agent, and the raw material components are difficult to heat-initiate cross-linking reactions during the mixing stage. The density of the cross-linked structure obtained by relying solely on radiation cross-linking is insufficient, resulting in a significant decrease in the mechanical properties, heat resistance, moisture and heat resistance, and corrosion resistance of the cable material.

[0117] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the cable material composition for offshore photovoltaics and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A cable material composition for offshore photovoltaics, characterized in that: The raw materials for preparing the cable material composition include the following components in parts by mass:

2. The cable material composition according to claim 1, characterized in that: The alkenyl cyclophosphazene compound has a structure as shown in Formula I: Wherein, R1, R2, R3, R4, R5, and R6 are each independently selected from any one of phenyl and C2-C10 alkenyl-substituted phenyl, and at least one of R1, R2, R3, R4, R5, and R6 is C2-C10 alkenyl-substituted phenyl; Preferably, R1, R2, R3, R4, R5, and R6 are each independently selected from phenyl, Any one of, and at least one of R1, R2, R3, R4, R5 and R6 is R is selected from vinyl, propenyl or allyl.

3. The cable material composition according to claim 1 or 2, characterized in that: The alkenyl oligomeric silsesquioxane includes any one of octavinyl cage-type oligomeric silsesquioxane, octamethacrylate cage-type oligomeric silsesquioxane, octaacrylate cage-type oligomeric silsesquioxane, octaacryloxy cage-type oligomeric silsesquioxane, octamethacryloxy cage-type oligomeric silsesquioxane, and methacryloxypropyl cage-type polysilsesquioxane, or a combination of at least two thereof; Preferably, the mass ratio of the alkenyl oligomeric silsesquioxane to the alkenyl cyclophosphazene-containing compound is 1:(3-8).

4. The cable material composition according to any one of claims 1 to 3, characterized in that: The polyethylene includes any one of linear low-density polyethylene, high-density polyethylene, and metallocene polyethylene, or a combination of at least two thereof, preferably a combination of high-density polyethylene and metallocene polyethylene; Preferably, the mass percentage of metallocene polyethylene in the polyethylene is 15-50%.

5. The cable material composition according to any one of claims 1 to 4, characterized in that: The butadiene-based polymer includes any one of polybutadiene and butadiene-styrene copolymer or a combination of at least two thereof; Preferably, the number average molecular weight of the butadiene-based polymer is 1000-10000; Preferably, the butadiene-based polymer comprises a structural unit represented by formula II, and the molar percentage of the structural unit represented by formula II in the butadiene-based polymer is 20-90%; Preferably, the mass ratio of the butadiene-based polymer to the thermoplastic elastomer is (0.5-2):1; Preferably, the thermoplastic elastomer includes POE elastomer and / or TPE elastomer, and POE elastomer is further preferred.

6. The cable material composition according to any one of claims 1 to 5, characterized in that: The compatibilizer includes any one of maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, maleic anhydride grafted ethylene propylene diene monomer rubber, and maleic anhydride grafted ethylene-vinyl acetate copolymer, or a combination of at least two thereof; Preferably, the cross-linking agent comprises an organic peroxide, preferably any one of cumene hydroperoxide, di-tert-butyl peroxide, diisopropylbenzene hydroperoxide, dibenzoyl peroxide, cyclohexanone peroxide, tert-butyl perbenzoate, tert-butyl peracetate, tert-amyl peroxy (2-ethylhexyl) carbonate, di (4-methylbenzoyl) peroxide, 2,5-dimethyl-2,5-di-tert-butyl peroxide ethane, tert-butyl peroxy-3,5,5-trimethylhexanoate or a combination of at least two thereof; Preferably, the auxiliary cross-linking agent includes any one of triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, tri(1,2-propylene glycol) diacrylate, tri(2-hydroxyethyl)isocyanuric acid triacrylate, propoxylated trimethylolpropane triacrylate, or a combination of at least two thereof; Preferably, the flame retardant includes any one of antimony trioxide, aluminum hydroxide, and magnesium hydroxide, or a combination of at least two of them.

7. The cable material composition according to any one of claims 1 to 6, characterized in that: The preparation raw materials also include any one or a combination of at least two of a stabilizer, a lubricant, a silane coupling agent, a mildew preventer, an ultraviolet absorber, and an antioxidant; Preferably, the raw material for preparation further comprises 0.1-5 parts of a stabilizer by weight; Preferably, the stabilizer includes any one of calcium stearate, magnesium stearate, zinc stearate, and pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) or a combination of at least two thereof; Preferably, the raw material for preparation further comprises 0.1-5 parts by mass of a lubricant; Preferably, the lubricant comprises any one of silicone masterbatch, silicone phenol, polyethylene wax, or a combination of at least two thereof; Preferably, the raw material for preparation further comprises 0.1-3 parts by mass of a silane coupling agent; Preferably, the silane coupling agent includes any one of a vinyl silane coupling agent, an epoxy silane coupling agent, an amino silane coupling agent, and a mercapto silane coupling agent, or a combination of at least two thereof; Preferably, the raw materials for preparation further include 0.1-5 parts of antifungal agent by weight; Preferably, the raw material for preparation further comprises 0.1-3 parts by mass of ultraviolet absorber; Preferably, the raw material for preparation further comprises 0.1-3 parts of antioxidant by mass.

8. A method for preparing the cable material composition according to any one of claims 1 to 7, characterized in that: The preparation method comprises: The prepared raw materials are mixed and extruded to obtain pellets; The pellets are made into wires through a wire extruder, and the wires are irradiated and cross-linked through an electron accelerator to obtain the cable material composition.

9. The preparation method according to claim 8, characterized in that: The mixing is carried out in an internal mixer; Preferably, the mixing temperature is 150-180°C and the mixing time is 5-30min; Preferably, the extrusion granulation is carried out in a screw extruder; Preferably, the operating temperature of the screw extruder is 100-150°C; Preferably, the working temperature of the wire extruder is 100-190°C; Preferably, the radiation cross-linking dosage is 2-10 Mrad.

10. Use of the cable material composition according to any one of claims 1 to 7 in an offshore photovoltaic module.

Citation Information

Patent Citations

  • Low smoke halogen-free flame retardant material applicable to photovoltaic cable and manufacturing method thereof

    CN103881166A

  • Anti-aging photovoltaic cable and preparation method thereof

    CN107141650A